Parto vacuum cleaner - Azmi, Amirul Haikal; Hamdan, Muhammad Amirul Shafiq; Zakaria, Muhammad Faiz Sharifudin; Ismail, Salwani; Mohammad Yusoff, Nurulhuda (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
Environmental pollution is a serious problem that threatens the survival of mankind. One of the activities that can reduce environmental pollution is by recycling waste materials. Recycling is the method of regaining, reprocessing, and reusing the waste materials that would be thrown away. The most commonly recycled materials include paper, glass, plastic, and metals. Using various types of waste materials, a simple, small size, battery operated and user-friendly portable vacuum cleaner was designed. This vacuum cleaner is suitable to be used by children to educate them about cleanliness and also by adolescents and adult especially when the cleaning involves the tiny surfaces or holes. The vacuum cleaner, Parto Vacuum Cleaner main components include an axial fan, dust compartment, sucker tube, and 9V DC. Since the construction of the Parto Vacuum Cleaner is simple, children can even do it by themselves (DIY method). Parto Vacuum Cleaner is an effective, simple and low-cost vacuum cleaner suitable to be used when cleaning tiny surfaces or holes has the potential to be patented and commercialized.